Equilibration and Increase of Hemoglobin Concentration after One Unit Whole Blood Transfusion among Patients Not Actively Bleeding (Journal of Dhaka Medical College, 2015)
Background: Transfusion is a specialized modality of patient management and lifesaving intervention. The decision to transfuse should be individualized, based on a rational approach and taking into account the hemoglobin value in addition to physiologic variables. The purpose of this study was to determine the amount of increase in haemoglobin levels and the rapidity of equilibration after single unit fresh whole blood transfusion in medical inpatients not actively bleeding among the Bangladeshi population.Methods: The present cross sectional study was conducted at the Department of Transfusion Medicine, Dhaka Medical College, Dhaka during the periods of July 2012 to June 2013. Total 100 purposively selected admitted patients in the Department of Medicine of Dhaka Medical College Hospital (DMCH) undergone blood transfusion were included in the study. Demographic characteristics were obtained from the clinical records and by face to face interview. Haemoglobin concentration was measured before transfusion, after 6 hours and 24 hours of transfusion using standard laboratory method. Data were analyzed using SPSS version 16 (SPPS Incorporation, Chicago, IL, USA). Comparison between mean values of haemoglobin was compared with students t-test and two-sided P value of 0.05 or less was considered significant.Results: The mean ±SD of the age of the respondents was 24.17±4.96 years with a range of 19 to 45 years and 90.0% were male and 10.0% were female. Previous blood donation history present in 72.0% respondents and absent in 28.0% respondents. Mean±SD of Hb level before, 6 hours and 24 hours after transfusion were 7.64±1.05, 8.03±1.07 and 8.78±1.19 gm/dl respectively. In the present study the mean increase of Hb 6 hours and 24 hours after transfusion were 0.39 gm/dl and 1.14 gm/dl respectively. Comparison between mean Hb level of before transfusion with 6 hours and 24 hours after transfusion revealed a statistically significant difference. Comparison between mean Hb level at 6 hours and 24 hours after transfusion also revealed a statistically significant difference.Conclusion: The study revealed slightly more one gram increase of Hb at 24 hours after transfusion of one unit of whole blood among patients not actively bleeding. There is significant difference between Hb level at 6 hours and 24 hours after transfusion.J Dhaka Medical College, Vol. 23, No.2, October, 2014, Page 161-166